"A Logic of Camps": French Antiracism as Competitive Nationalism. Issue 1 (May 2015) - Tejani, Riaz
<x xml:space="preserve">Abstract</x> As the Charlie Hebdo and Copenhagen attacks starkly remind us, European multicultural policy continues to falter over the growth of public Islam. But long before these events, tension between competing visions of citizenship and nationhood had weakened the very civil society organizations that could shape such policy. In France, where non‐governmental organizations had labored against discrimination for over a century, this conflict led to profound disaffection within the nation's powerful antiracism movement. Drawing from more than two years of ethnographic fieldwork among French antiracist NGOs, this article examines that disaffection among activists whose work in the name of cultural outsiders simultaneously served to rememorialize historic national traumas from the Dreyfus Affair to Algeria. Revealing a new despondency over sociolegal advocacy for Islam, some decried "infiltration" of communitarian voices into their erstwhile republican movement while others, under increasing pressure to adopt an emergent pluralist vision, equated this new model with foreignness itself. The resulting "crisis of antiracism" saw competitive reassertions of nationhood in the face of countervailing state discourses of European postnationalism. If writings on French multiculturalism to date have focused on Islamic piety and urban youth deviance, this article examines the significant impact these have had on France's preeminent social justice movement.